2010
DOI: 10.1007/s12192-010-0203-0
|View full text |Cite
|
Sign up to set email alerts
|

Anti-heat shock protein 70 autoantibody epitope changes and BD091 promotes atherosclerosis in rats

Abstract: It has been previously reported that the plasma levels of autoantibodies against heat shock protein 70 (HSP70) are elevated in atherosclerosis. The aim of the present study was to elucidate whether anti-HSP70 antibodies are involved in the pathogenesis of atherosclerosis. To determine this, we chose rats as an atherosclerosis model. Titers of plasma anti-HSP70 autoantibody were determined by ELISA. After the intravenous administration of antibody into the tail, the damaged areas of aorta were stained with Evan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…As in our previous studies (Leng et al 2010(Leng et al , 2013, we successfully induced atherosclerotic pathological changes in rats' thoracic aorta accompanied by a significant elevation of plasma TC, LDL, Hcy, and most importantly by circulating HSP70. The increased plasma HSP70 probably derived from multiple cells.…”
Section: Discussionmentioning
confidence: 78%
“…As in our previous studies (Leng et al 2010(Leng et al , 2013, we successfully induced atherosclerotic pathological changes in rats' thoracic aorta accompanied by a significant elevation of plasma TC, LDL, Hcy, and most importantly by circulating HSP70. The increased plasma HSP70 probably derived from multiple cells.…”
Section: Discussionmentioning
confidence: 78%
“…Twelve rats given a normal diet were designated as a sham group, and the other 36 rats were fed with a high-cholesterol diet for 10 weeks to induce atherosclerosis. 14 15 The high-cholesterol diet contained 3% cholesterol, 0.5% cholic acid, 0.2% 6-propyl 2-thiouracil, 5% sucrose, and 3% lard. Subsequently, the 36 hyperlipidemic rats were randomly and evenly assigned to three groups: a control group that was administered normal saline, a low-dose darapladib group that received darapladib by gavage (25 mg·kg -1 ·d -1 , reconstituted in normal saline), and a high-dose darapladib group that received darapladib by gavage (50 mg·kg -1 ·d -1 , reconstituted in normal saline).…”
Section: Methodsmentioning
confidence: 99%
“…To analyze whether Hsp70 was present within the membrane preparation, the PVDF membranes were blocked for 2 h at room temperature with 3 % gelatin in Tris-buffered saline (500 mmol/L NaCl and 20 mmol/L Tris, pH8.0), and then incubated with mAb against Hsp70 (BD091, 1:80 in Tris-buffered saline containing 1 % gelatin and 0.05 % Tween 20) (Leng et al, 2010), HSC70 (SPA-815, Stressgen) for overnight at 4°C. The purity of the fractions was tested using HSC70 antibody which detected HSC70 in the cytoplasmic fraction but not in the membrane fraction.…”
Section: Membrane Preparation and Western Blottingmentioning
confidence: 99%
“…We have previously shown that anti-Hsp70 antibody (BD091) promotes atherosclerosis in rats (Leng et al 2010). An important question that remains unanswered is how does BD091 promote atherosclerosis?…”
Section: Introductionmentioning
confidence: 99%